2013
DOI: 10.1542/peds.2012-4029
|View full text |Cite
|
Sign up to set email alerts
|

Improving Screening for Cystic Fibrosis–Related Diabetes at a Pediatric Cystic Fibrosis Program

Abstract: OBJECTIVE: Despite guidelines recommending an annual oral glucose tolerance test (OGTT) for all patients with cystic fibrosis (CF) aged $10 years, screening rates for cystic fibrosis-related diabetes (CFRD) remained low at our center. The aim of this project was to implement an outpatient system to provide effective, evidence-based screening for CFRD at a pediatric CF program.METHODS: Development of a system to improve outpatient screening for CFRD included structured education, communication with families, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…The advantage is the potential to improve the sensitivity of this clinical test; the limitations are in cost and more intensive testing for patients and healthcare teams. Adherence to OGTT screening is already <50% at many centres [2,25,28,33], mainly due to perceived burden from both sides [19]. We found that a five time point OGTT provided better assessment of CFRD risk but its applicability in a clinical setting needs to be established.…”
Section: Discussionmentioning
confidence: 92%
“…The advantage is the potential to improve the sensitivity of this clinical test; the limitations are in cost and more intensive testing for patients and healthcare teams. Adherence to OGTT screening is already <50% at many centres [2,25,28,33], mainly due to perceived burden from both sides [19]. We found that a five time point OGTT provided better assessment of CFRD risk but its applicability in a clinical setting needs to be established.…”
Section: Discussionmentioning
confidence: 92%
“…Genetically determined function of the remaining b-cells and insulin resistance associated with infection and inflammation may also play a role. Encouraging data suggest that improved screening (544,545) and aggressive insulin therapy have narrowed the gap in mortality between cystic fibrosis patients with and without diabetes, and have eliminated the sex difference in mortality (546). Recent trials comparing insulin with oral repaglinide showed no significant difference between the groups.…”
Section: Drugs Contraindicated In Pregnancymentioning
confidence: 99%
“…The OGTT is a time-consuming test requiring overnight fasting, hence overall screening rates remain low in the US. There are several patient barriers associated with low screening rates including need for prolonged fasting, separate and long appointment times, and insufficient awareness about the importance of screening [27] , [28] .…”
Section: Screening and Diagnosismentioning
confidence: 99%